A framework to select strategies for conserving and restoring habitat connectivity in complex landscapes. Issue 6 (20th April 2022) - Cameron, D. Richard; Schloss, Carrie A.; Theobald, David M.; Morrison, Scott A.
Abstract: Protecting or restoring habitat connectivity in landscapes undergoing rapid environmental change requires multiple conservation and restoration strategies. These strategies have different risk profiles, costs, and require various types of technical expertise to conduct. This diversity in landscape context and strategic approach requires more nuance and flexibility than traditional connectivity conservation plans have supported. We present a novel, spatially‐explicit framework for developing connectivity conservation priorities and strategies based on Omniscape, an adaptation of Circuitscape, a common tool for mapping habitat connectivity. Using California (USA) as a case study, we mapped structural connectivity and developed a classification of connectivity conservation and restoration categories across the gradient of land use intensities, as well as by land ownership. The most constrained areas with highly concentrated flow (movement potential) make up 3% of the state and occur primarily on private lands. Conversely, intact areas with diffuse flow that indicate multiple connectivity options cover 55% of the state, including the majority of the desert and mountain ecoregions. This "strategy mapping" approach can be used to identify priority areas for conservation investment and suites of potential implementation mechanisms and partners, which in turn may improve the efficiency and effectiveness of connectivity conservation in this era of global change. Abstract : Conserving and restoring habitat connectivity in complex landscapes requires diverse skills, strategies, and partnerships. We present a strategy mapping framework for connectivity using a novel model and illustrate its application in California.